Designing Information Systems to Support Habit Formation : From Theories to Design Principles - Chung, Alexander Quoc Huy (Université d'Ottawa / University of Ottawa, 2022)
Sustaining behaviour change is fundamental for the effective uptake of policies and practices aimed at improving individual and collective health, yet it can be very difficult for individuals to adhere to new desired health-related behaviours. A prospective solution is to focus on instilling these behaviours as a habit. Once instilled as a habit, behaviours are performed automatically given specific cues, and they relieve the cognitive stress of having to make a volitional decision towards performing the behaviour - making it more resistant to relapse. Several information systems (IS) are being proposed to help individual users instil target behaviours as habits so that they can be performed even when intentions shift. However, these systems tend to be designed in an ad hoc manner and, as a result, their effectiveness can vary substantially. To better guide the design of information systems that can support users in forming health-related behaviours as a habit, we define a subclass of systems called Habit Formation Support Systems (HFSS) and adopt the design science research approach to develop two artifacts: (1) a design-relevant theory explaining and predicting how IS-supported habit formation can be achieved called the Theory for the Formation of IS-Supported Habits (T-FISSH); and (2) a suite of design principles to guide the design of systems that can effectively support users in forming a desired health-related behaviour as a habit. We contend that habit theory and IS continuance theory can be used to anchor the development of the two artifacts. The T-FISSH was refined and validated using exploratory and confirmatory focus groups with academics and health behaviour change practitioners respectively. The design principles were refined with systems design and development professionals and validated through a reusability check that involved a design activity and reusability questionnaire. The theoretical contribution of the thesis lies in moving the habit formation knowledge base into the design realm through the development of a design-relevant explanatory/predictive theory. From a practical perspective, this research presents a suite of theory-anchored design principles that are intended to guide the design and development of systems that can support users in forming desired health-related behaviours as a habit.
Keywords: Management Information Systems; Design Science Research; Design Principles; Persuasive Systems; Behaviour Change; Habit Formation